The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1017/s1759078721000684
|View full text |Cite
|
Sign up to set email alerts
|

Wideband split-ring antenna arrays based on substrate integrated waveguide for Ka-band applications

Abstract: This paper presents wideband split-ring antenna arrays based on substrate integrated waveguide (SIW) for Ka-band (26.5–40 GHz) applications. The antenna array is fed by a 2.92 mm coaxial connector (K-connector) and the power is equally distributed to each split-ring resonator. The designed coplanar waveguide (CPW), SIW, CPW-to-SIW transition, coaxial-to-CPW transition, and two-stage SIW power divider are described in detail. By using a thin Rogers 6002 substrate with silver epoxy-filled vias, a transition prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…A novel wideband SIW based split-ring resonator antenna has been reported in [96]. The detailed design descriptions of the coaxial to CPW and CPW to SIW transition have been demonstrated.…”
Section: Performance Improvement Of Siw Based On-chip Antennas In Thz...mentioning
confidence: 99%
See 4 more Smart Citations
“…A novel wideband SIW based split-ring resonator antenna has been reported in [96]. The detailed design descriptions of the coaxial to CPW and CPW to SIW transition have been demonstrated.…”
Section: Performance Improvement Of Siw Based On-chip Antennas In Thz...mentioning
confidence: 99%
“…Smooth propagation modes conversion from coaxial to CPW and CPW to SIW is necessary to obtain wideband performance. The E field distribution (Figure 6 in [96]) in the designed back-to-back transition prototype has shown that the coaxial mode has been generated at the input terminal (at the connector), CPW mode generated at the end of the coaxial to CPW transition, and finally, the SIW mode generated at the end of the CPW to SIW transition. Hence, the designed transition has exhibited a wider impedance bandwidth (26 GHz to 40 GHz).…”
Section: Performance Improvement Of Siw Based On-chip Antennas In Thz...mentioning
confidence: 99%
See 3 more Smart Citations